2010
DOI: 10.1152/ajpheart.00331.2010
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin enhances hydrogen peroxide-mediated dilatation of canine coronary collateral arterioles during myocardial ischemia in dogs in vivo

Abstract: Erythropoietin enhances hydrogen peroxide-mediated dilatation of canine coronary collateral arterioles during myocardial ischemia in dogs in vivo. We have previously demonstrated that endothelium-derived hydrogen peroxide (H 2O2) plays an important role in the canine coronary microcirculation as an endothelium-derived hyperpolarizing factor in vivo. However, it remains to be examined whether endogenous H 2O2 is involved in the dilatation of coronary collaterals during myocardial ischemia in vivo and, if so, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(66 reference statements)
3
5
0
Order By: Relevance
“…Coronary microcirculation plays an important role in maintaining blood flow and vascular homeostasis under both physiological and pathological conditions. We have confirmed that EDH plays an important compensatory role during coronary autoregulation and reperfusion injury in ischemic and collateral microcirculation in dogs in vivo through compensation of NO. Endothelial dysfunction has been implicated in the reduced dilatation of porcine coronary microcirculation .…”
Section: Introductionsupporting
confidence: 70%
“…Coronary microcirculation plays an important role in maintaining blood flow and vascular homeostasis under both physiological and pathological conditions. We have confirmed that EDH plays an important compensatory role during coronary autoregulation and reperfusion injury in ischemic and collateral microcirculation in dogs in vivo through compensation of NO. Endothelial dysfunction has been implicated in the reduced dilatation of porcine coronary microcirculation .…”
Section: Introductionsupporting
confidence: 70%
“…Erythropoietin (EPO) reduces oxidative stress and facilitates NO production (and also that of H 2 O 2 ; see section ) and thus prevents endothelial dysfunction resulting from eNOS uncoupling both in vivo and in vitro (Yada et al . , Kuriyama et al . , d'Uscio et al .…”
Section: Nitric Oxidementioning
confidence: 99%
“…Tetraethylammonium-sensitive K + channels (BK Ca or K V ) in the coronary microvasculature are redox-sensitive targets in the cardioprotective effect of endogenous H 2 O 2 during ischemia-reperfusion injury (997). In the dog heart, erythropoietin enhances the H 2 O 2 - and BK Ca -mediated dilation of coronary collateral arterioles during ischemia (999). Redox-sensitive K V (but not BK Ca ) channels mediate H 2 O 2 -induced vasodilation in canine coronary arterioles and in the canine heart in vivo (799).…”
Section: Ion Channels As End Effectorsmentioning
confidence: 99%